Edible Oils Attenuate Button Battery-Induced Injury in Porcine Esophageal Segments - Jia, Wenyuan; Zhang, Bin; Xu, Guanghui; Xie, Jiangang; Wei, Haidong; Shan, Niqi; Wang, Qianmei; Yin, Wen; Zhao, Wei (Frontiers in Pediatrics, 2020)
Objective: The objective of the study is to test whether the use of edible oil might be an early treatment strategy for reducing button battery-induced esophageal injury. Methods: A button battery was inserted into esophageal segments collected from pigs. The esophageal segments were randomly allotted to one of the following six treatments: 1) untreated (nothing injected), 2) lemon juice, 3) orange juice, 4) colza oil, 5) peanut oil, and 6) olive oil. Every hour, the battery discharge and the pH value were measured in the esophageal tissue. After treatment for 6 hours, the residual voltage of the battery was measured and the esophageal tissue was processed with H&E staining. Results: In esophageal segments of the untreated group, a large area of the mucous membrane was severely eroded. Partial erosion was observed in esophageal tissues treated with either lemon juice or orange juice. Furthermore, the esophageal tissues were basically intact, had little damage when treated with oils. The highest extra-esophageal discharge voltage was recorded in the untreated group, a medium amount of discharge voltage was recorded in the lemon juice and orange juice groups, and the lowest discharge voltage was recorded in all the edible oils groups. Conclusions: Edible oils immersed the battery, reduced the surrounding electrolysis, and thus attenuated battery discharge. As a result, treatment with edible oils attenuated the pH alkalization and tissue damage in button battery injury of pig esophageal segments. These results indicate that edible oils might be used in the treatment of button battery ingestion.